Research on the Development of Daily Clothing Sets for Teenage Girls from BI-Component Knitted Fabrics - Khilola Tursunova; Shokhjakhon Fozilov (Periodica Journal, 2022)
The article talks about the collection of teenage girls' clothes, the collection of world brands, the production of clothes that are typical and suitable for our mentality, and the offer of fabrics. The article provides detailed information about what will be the fashion for teenagers and children in 2019-2020
Keywords: Modern fashion; fashion features; global brands; modern clothing styles